"By What Authority?": Women Writing in the Seventeenth Century - Bowerbank, Sylvia (My University, 1985)
This thesis attempts to reconcile a feminist with a contextualist approach. It enquires into the historical origins of the emergence of women as writers in the seventeenth century. At the same time, it places this women's movement in the context of a profoundly complex revolution in thought, thereby discovering that women's intellectual contributions to the destruction of the hierarchical world view and to the search for new, just alternatives were as diverse and as problematic as men's were. The women who wrote in the seventeenth century were all preoccupied, implicitly or explicitly, with the question: By what authority do I cast off the traditional silence of women and dare to speak out? They gave different answers. Part One uses the lives of Gertrude More and Mary Ward to illustrate the subtle ways in which the Catholic Church's concept of grace required the submission of women despite their conflicting inner voices. In contrast, Part Two explores the challenge of the seventeenth-century chariasmatic movement to the traditional notion of grace. The radical female Protestants made a significant step towards modern feminism both because they appealed to their own experience as a source for truth and because they initiated an autobiographical form which dramatizes the convinced woman in revolt against patriarchal structures. Part Three demonstrates that, despite the decline in the authority of the prophet's experience which came with the trliumph of the perspective and methods of science, Jane Lead's writings continued a mystical counter-tradition which would nourish the Romantic alternative to scientific reductionism. Part IV analyzes the views of Margaret Cavendish and Aphra Behn who argued the natural right of a woman to write. Both challenged neoclassical aesthetic ideals--Cavendish by writing to delight herself, Behn by writing to delight her audience. Part V concludes by contrasting the approaches of two women who appealed to the authority of rational argument to justify their views. Mary Astell emerges as an early theorist for enlightenment feminism, Anne Conway as a theorist for holistic feminism.
Keywords: feminist, contextualist, origins, women, writers, seventeenth century, hierarchial world view, feminism, conflicting